The Coronavirus Intervention in Ethiopia and the Challenges for Implementation - Nigussie, Hagos (Frontiers in Communication, 2021)
The coronavirus has been rapidly spreading across different parts of the globe. The pandemic will have a severe impact unless coordinated preventive measures are undertaken. This paper examines the COVID-19 intervention and the challenges for implementation in Mekelle, Tigray, northern Ethiopia. Telephone interviews, personal observation and document reviews were used as data collection techniques. Results showed that the majority of the population in Mekelle are aware of the pandemic. Most people practiced handwashing with soap and water. But there is limited physical distancing in religious institutions, market places, and coffee houses where many people convene. With this, staying at home remains a challenge among the majority. Still, there is a belief that the pandemic is a “punishment from God”, while others believe that it is an illness of the old and does not affect the young. Generally, applying the recommended COVID-19 prevention measures, including the physical distancing, seem unattainable as the majority continue to overlook government advice. As related studies such as the fight against the Ebola outbreak in West African countries showed, this emanates from the lack of trust in media messages. In Tigray, religious leaders and community elders have a significant influence on their respective community members. Messages from these individuals remain trusted and can easily reach the majority due to social networks. This highlights that besides enforcing strict and prolonged measures from the government, reliable two-way communication can help achieve the desired behavior changes towards complying with the COVID-19 prevention measures among the different segments of the population in Mekelle.